THEORETICAL AND METHODOLOGICAL BASIS OF THE ACTIVITIES OF DESTRUCTIVE AND TOTALITARIAN SECTS IN THE CONDITIONS OF GLOBALIZATION - Куранов Умид Мухаммадович (Innovate Conferences, 2025)
This article provides a detailed analysis of the theoretical and methodological foundations of destructive and totalitarian sects in the context of globalization. The impact of globalization on social, economic, and cultural processes increases the proliferation of sects, threatening the stability of society and harming the mental health of their members. The article discusses definitions of destructive and totalitarian sects, their psychological, sociological, and religious foundations, and theories related to globalization. Research methods, data collection, analysis, and ethical aspects are examined methodologically.
Keywords: Globalization, destructive sects, totalitarian sects, theoretical foundations, methodological foundations, psychological control, prevention, spread of sects, migration, Internet.